An Investigation into the Factors that Affect Miscommunication between Pilots and Air Traffic Controllers in Commercial Aviation. Issue 1 (3rd April 2019) - Wu, Qiong; Molesworth, Brett R. C.; Estival, Dominique
ABSTRACT: Objective: The present research sought to investigate the communication performance of both native English sounding pilots and accented commercial pilots in two different phases of flight, the approach and departure phase of flight. Background: English language proficiency requirements, standardized phraseology, and readbacks are some of the proactive measures which the aviation industry employs to ensure effective communication. However, despite these efforts, errors in communication still occur, and anecdotal evidence suggests that factors such as language background and phase of flight increase the likelihood of communication errors. Method: Eighteen hours of air-ground communications at Kingsford Smith International Airport, Sydney, Australia, were analyzed. Results: The results revealed that accented pilots committed more communication errors than native English sounding pilots and more specifically that these errors were mistakes rather than omissions, and involved words rather than numbers. Communication performance was similar in the approach and departure phases of flight regardless of language background. Conclusion: These results provide detailed information about the type of communication errors which occur in commercial aviation, their prevalence and the context in which they occur, which helps guide where resources should be directed to further improve safety.